A novel unknown-input and single-output approach to extract vibration patterns via a roving continuous random excitation. (October 2022) - Yang, Zhuozheng; Pan, Jun; Chen, Jinglong; Zi, Yanyang; Oberst, Sebastian; Schwingshackl, C.W.; Hoffmann, Norbert
Abstract: Operating deflection shape analysis allows investigating the dynamic behaviour of a structure during operation. It normally requires simultaneous, multi-point measurements to capture the response from an unknown excitation source (unknown-input and multiple-output), which can complicate its usage for structures without ease of access. A novel vibration pattern testing method is proposed based on a roving continuous random excitation employing a small robotic Hexbug device and a single-point measurement. The Hexbug introduces a random excitation in consecutive locations while roaming over the structure. The resulting multi-modal, time and location dependent response of the system is captured in a single location, and then analysed with a newly developed method based on empirical wavelet transform, multiscale morphological filtering and optimization to extract the excited vibration patterns. The efficiency of the proposed method is experimentally demonstrated on a free–free and a cantilevered beam with comparison to mode shapes extracted by hammer test. The validation highlights its ability to extract several vibration patterns from a long slender structure with good accuracy and robustness, with the general ability to expand the usability of an operating deflecting shape analysis. Highlights: It is proposed to use a small robotic device that roves around a structure to measure its Operating Deflection Shapes. An advanced data post-processing routine based on the combination of Empirical Wavelet Transform and Multiscale Morphological Filtering is proposed. Two different beam setups are tested to verify the effectiveness and repeatability of the proposed method. The proposed method provides an alternative way to measure Operating Deflection Shape of long slender structures with a simple and cheap setup.